Strategi Marketing Public Relations Mandy’s Shoes Dalam Meningkatkan Brand Awareness Di Pasar Indonesia - Sarah Elvira; Lina Sinatra Wijaya (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
The fashion industry, especially women's shoes, faces increasingly fierce competition in the digital age, requiring companies to have effective marketing communication strategies to increase brand awareness. Mandy's Shoes is a local women's shoe brand that focuses on comfort and fashionable designs, but still faces challenges in increasing brand awareness in the Indonesian market. This study aims to analyze the Marketing Public Relations strategy implemented by Mandy's Shoes and to determine the brand's awareness in the Indonesian market. This study uses a mixed-methods approach, combining qualitative and quantitative methods. Qualitative data was obtained through in-depth interviews with Mandy's Shoes internal parties and consumers, as well as documentation of Instagram social media content. Quantitative data were collected through the distribution of questionnaires to 52 respondents aged 18–45 years residing in big cities and active on social media. Data analysis was conducted descriptively and compiled to obtain a more comprehensive pictureThe results of the study show that Mandy's Shoes' brand awareness is strongest in brand recall, but its top-of-mind awareness remains relatively low. Mandy's Shoes' Marketing Public Relations strategy is implemented through push and pull strategies. The push strategy is carried out through participation in offline events, digital promotions, Instagram Ads, and collaborations with influencers and KOLs. The pull strategy is implemented through Instagram optimization, storytelling content, discount promotions, and visual designs consistent with the brand image. Meanwhile, the pass strategy has not been implemented due to a lack of involvement in social or community activities. This study concludes that the Marketing Public Relations strategy implemented by Mandy's Shoes is quite effective in building brand awareness up to the brand recall stage. However, communication strategies and the implementation of a pass strategy still need to be strengthened to improve the brand's position and achieve top-of-mind status in the Indonesian market.